Volunteering is prospectively associated with health care use among older adults. (January 2016) - Kim, Eric S.; Konrath, Sara H.
Abstract: Rationale: Although observational and experimental studies have shown that volunteering is linked with better mental health, physical health, and health behaviors, no studies have examined whether volunteering is associated with patterns of health care use. Objective: The purpose of this study was to prospectively examine whether volunteering was associated with a greater use of preventive health care services, but fewer doctor visits and nights spent in the hospital. Methods: Participants ( n = 7168) were drawn from the 2006 wave of the Health and Retirement Study, a nationally representative panel study of American adults over the age of 51, and tracked for one wave (2 years). Logistic regression and generalized linear models were used for analyses. Results: In analyses that adjusted for sociodemographic factors and baseline health, volunteers were 30% more likely to receive flu shots ( OR = 1.30, 95% CI = 1.16–1.47), 47% more likely to receive cholesterol tests ( OR = 1.47, 95% CI = 1.24–1.74); female volunteers were 53% more likely to receive mammograms/x-rays ( OR = 1.53, 95% CI = 1.28–1.83) and 21% more likely to receive Pap smears ( OR = 1.21, 95% CI = 1.03–1.41); male volunteers were 59% more likely to receive prostate exams ( OR = 1.59, 95% CI = 1.29–1.95). In a model that adjusted for sociodemographic factors, volunteers spent 38% fewer nights in the hospital ( RR = 0.62, 95% CI = 0.52–0.76), however volunteering was not associated with frequency of doctor visits ( RR = 0.94, 95% CI = 0.87–1.02). The association between volunteering and number of nights spent in the hospital was minimally affected after adjusting for potential confounding (baseline health) and explanatory variables (health behaviors, social integration, stress, positive psychological factors, personality). Conclusion: This is the first known study to examine the association between volunteering and health care use. If future studies replicate these findings, the results may be used to inform the development of new strategies for increasing preventive health screenings, lowering health care use and costs, and enhancing the health of older adults. Highlights: Past studies show that volunteering is linked with better health and behaviors. We examined the link between volunteering and health care use two years later. Data were from a nationally representative sample of U.S. adults aged 51 and over. Volunteers were more likely to use preventive health care services. Volunteers spent fewer nights in the hospital but did not make fewer doctor visits.